Estimated small dense low-density lipoprotein-cholesterol and the risk of kidney and cardiovascular outcomes in diabetic kidney disease - Qing Yang; Yutong Zou; Yanlin Lang; Jia Yang; Yucheng Wu; Xiang Xiao; Chunmei Qin; Yuancheng Zhao; Fang Liu (Renal Failure)
Aims This study aimed to investigate the correlations between estimated small dense low-density lipoprotein-cholesterol (esd-LDL-c) and the development of end-stage kidney disease (ESKD), cardiovascular mortality, and all-cause mortality in individuals with diabetic kidney disease (DKD) or diabetes mellitus (DM) concomitant chronic kidney disease (CKD).Methods We analyzed the data from a biopsy-proven DKD cohort conducted at West China Hospital of Sichuan University between 2009 and 2021 (the DKD cohort) and participants with DM and CKD in the National Health and Nutrition Examination Survey (NHANES) 2011–2014 (the NHANES DM-CKD cohort). Cox regression analysis was also used to estimate associations between esd-LDL-c and the incidence of ESKD, cardiovascular mortality, and all-cause mortality.Results There were 175 ESKD events among 338 participants in the DKD cohort. Patients were divided into three groups based on esd-LDL-c tertiles (T1 < 33.7 mg/dL, T2 ≥ 33.7 mg/dL to <45.9 mg/dL, T3 ≥ 45.9 mg/dL). The highest tertile of esd-LDL-c was associated with ESKD (adjusted HR 2.016, 95% CI 1.144–3.554, p = .015). Furthermore, there were 99 deaths (39 cardiovascular) among 293 participants in the NHANES DM-CKD cohort. Participants were classified into three groups in line with the tertile values of esd-LDL-c in the DKD cohort. The highest tertile of esd-LDL-c was associated with cardiovascular mortality (adjusted HR 3.95, 95% CI 1.3–12, p = .016) and all-cause mortality (adjusted HR 2.37, 95% CI 1.06–5.32, p = .036).Conclusions Higher esd-LDL-c was associated with increased risk of ESKD in people with biopsy-proven DKD, and higher cardiovascular and all-cause mortality risk among those with DM-CKD.